Creating Learner-Generated Audio and Audiovisual Content to support personal learning activities: making the transition from consumer to prosumer - Davis, Charles (2010)
This study explores the challenges faced by a cohort of five adult distance learners on a BSc in Psychology course when creating audio and audiovisual content to support personal learning activities. It describes how the design processes provided them with learning environments in which to exploit multiple digital and information literacies in an effort to create multimodal designs reflective of their needs as learners. The study provides valuable insights into how the participants employed a range of Web 2.0 offline and mobile technologies to mediate their meaning making activities. The findings illustrate that while the participants faced numerous challenges, they found adopting the role of designers a relatively comfortable one. However, evidence exists highlighting how the mediating presence of an expert and help resources played an important role in scaffolding the participants’ activities so that they finished the study feeling it was a positive experience. Taking the findings and the participants’ reflections into account, areas for further research are considered. These include how approaches to learning encouraging the creation of learner-generated content (LGC) might support collaborative activities as well as provide tutors with resources to distribute among future cohorts.